Internet of Things (Iot) Based Temperature and Humidity Monitoring System in the Chemical Laboratory of the Samarinda Industry Standardization and Research Center - Muhammad Awaludin; Andi Yusika Rangan; Amelia Yusnita (TEPIAN, 2021)
Temperature and humidity are important things in a chemical laboratory. By utilizing the internet, operators can remotely monitor laboratory temperatures and humidity with the Internet of Things (IoT) system. The Internet of Things (IoT) system can make it easier for operators to monitor temperature and humidity in chemical laboratories wherever and whenever. DHT11 sensor which functions as a temperature and humidity detector, NodeMCU ESP8266 microcontroller which functions as a data processor so that the DHT11 sensor detection results can be displayed on the monitoring website so that operators can see directly the results of temperature and humidity measurements at the chemical laboratory. This research was conducted at the Samarinda Industrial Research and Standardization Center. Data collection methods used are literature study, interviews, and observations. While the system development method used is prototype. As well as the supporting software used by the Arduino Integrated Development Environment, XAMPP, and Sublime.